2021
DOI: 10.3390/jmse9030337
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Microplastics in North-Western Mediterranean Harbors: Seasonality and Biofilm-Related Metallic Contaminants

Abstract: The Mediterranean Sea is one of the most impacted basins in terms of microplastics pollution. Land-based activities are the major sources of plastic litter to the ocean, with harbors probably representing significant hotspots. In the framework of the SPlasH! project (Stop alle Plastiche in H2O, Interreg Marittimo project), microplastics were sampled in three north-western Mediterranean harbors during summer and winter. In this study, the areal concentrations of microplastics ranged from 5576 to 379,965 items·k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Baini et al [35] also suggested an increase in MP concentration from coastal areas to distant waters. Other authors [25] emphasized the potential role of harbors in contributing to MPs in marine environments. We found no statistically significant differences in the MP abundance between the sites (p > 0.05).…”
Section: Physical-chemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Baini et al [35] also suggested an increase in MP concentration from coastal areas to distant waters. Other authors [25] emphasized the potential role of harbors in contributing to MPs in marine environments. We found no statistically significant differences in the MP abundance between the sites (p > 0.05).…”
Section: Physical-chemical Parametersmentioning
confidence: 99%
“…It was reported that over 701 marine species ingested MPs [15]. Many studies have demonstrated the long persistence and abundance of MPs [16,17], their unique reactivity and bioavailability for aquatic organisms [18], binding and absorbing of other chemical pollutants from aqueous media [19][20][21][22][23][24][25], and, thus, increasing the potential risk to ecosystems and human population. The estimate of 1.2 million tons of plastic stock that has accumulated in the Mediterranean Sea underscores the severity of plastic pollution [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ports represent an additional source of MPs in local waters and the open sea due to their intensive industrial and transport activities. Currently, despite evidence indicating a substantial impact of MP pollution on port ecosystems, its level remains inadequately characterised [62,63].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 2000s, attention on microplastics has grown exponentially (Schmid et al 2018) and there are many researchers and teams conducting studies on microplastic sampling and characterisation in environment (Gago et al 2018;Yu et al 2019), their effects on animals (Lusher et al 2017) and humans (Campanale et al 2020), and investigating their relationship with pollutants, such as metals, hydrocarbons etc. (Constant et al 2019;Kutralam-Muniasamy et al 2021;Pereao et al 2020;Tesán Onrubia et al 2021). In marine environment, microplastics are sought in the beach areas (Antunes et al 2018;Bosker et al 2017;Browne et al 2011;Constant et al 2019;Pieper et al 2019) and at different depth from the sea surface along the water column (Andrady 2011;Bagaev et al 2018;Baini et al 2018;Pan et al 2019;Zheng et al 2019) and down to sediments (Anderson et.…”
Section: Introductionmentioning
confidence: 99%